A road less traveled in nostalgia marketing: impact of spiritual well-being on effects of nostalgic advertisements. Issue 3 (3rd July 2021) - Singh, Ramendra; Sharma, Yukti; Kumar, Jitender
ABSTRACT: Spiritual well-being plays an integral role in the reconstruction of past events. In this direction, the current study investigates how differences in individuals' spiritual well-being elicit different cognitive and emotional responses to nostalgic ads. And how such differences in spiritual well-being lead to the different purchase intention of nostalgic products. We displayed a series of old Indian ads to respondents and found spiritual well-being influenced ad-evoked nostalgia and purchase intention of nostalgic products positively. Our study contributes to a road less traveled in nostalgia marketing and necessitates marketers to consider audiences' spiritual well-being before applying nostalgic appeal.